Modeling and predictive control of InGap/GaAs/Ge triple-junction solar cells to increase the energy conversion efficiency - Reza Barati-Boldaji; Sepide Mojalal; Mohammad Reza Seifi (Institute of Advanced Engineering and Science, 2019)
Physical studies of the last decade indicate that multi-junction solar cell has higher energy conversion efficiency than single-junction cells. However, choosing the type of material, modeling and finding the parameters of this type of cell has always been one of the leading challenges in this topic. Most of the proposed models are assumed to have predetermined electrical parameters of the cell or regardless of the effect of the tunnel junction, which reduces of the system. This paper discusses the modeling of solar cell triplejunction InGap/GaAs /Ge, taking into account the effect of a tunnel junction and finds the parameters of each subcellular deal. Also, predictive control will be used to control the active and reactive power of the single-phase inverter. The use of this method eliminates the need for the modulation module and the phase-lock loop (PLL). And simplifies the control algorithm for its digital implementation. The proposed cost function of this paper will be such that in addition to controlling the power of the inverter, the closed loop stability will be guaranteed based on the Lyapunov theory. Finally, the performance of the system using the software MATLAB/SIMULINK simulation will be evaluated.